Effects of tripotassium dicitrato bismuthate (TDB) tablets or cimetidine in the treatment of duodenal ulcer. Issue 12 (December 1983) - Hamilton, I; Worsley, B W; O'Connor, H J; Axon, A T
Abstract : Forty patients with duodenal ulcer were randomly allocated to treatment with either tripotassium dicitrato bismuthate tablets or cimetidine for six weeks. Endoscopically confirmed healing of the ulcer occurred in 80% treated with tripotassium dicitrato bismuthate tablets and in 85% treated with cimetidine. Symptomatic improvement was also similar in the two groups. Treatment with cimetidine was associated with an increase in pH of gastric aspirate during treatment and increased numbers of bacteria were isolated from the gastric aspirate during treatment, while the pH and bacterial flora of gastric aspirate did not change during tripotassium dicitrato bismuthate treatment. Serum and urinary bismuth levels rose during treatment with tripotassium dicitrato bismuthate and urinary excretion remained raised two weeks after cessation of treatment. Tripotassium dicitrato bismuthate tablets appear to be as effective as cimetidine in the treatment of duodenal ulcer without the potentially undesirable effects of a reduction in gastric acid secretion.